All-on-Four case rehabilitated with fully digitally fabricated prosthesis milled from graphene-reinforced poly methyl methacrylate puck using indigenously developed intraoral and extraoral scanning methods - Anil Goud Maddikunta; Siddharth Vaish (Wolters Kluwer Medknow Publications, 2023)
Digital dentistry is disruptive to conventional methods for performing prosthetic rehabilitation. Fabrication of prosthesis for all-on-four implants involves multiple steps when done conventionally and is prone to error. The use of digital technologies such as intraoral scanners (IOS) and extraoral scanners can marginalize these errors and also reduce the chairside time. This clinical report outlined a method which used a conjunction of extraoral and IOS to collect data for implant position, soft tissue profile, and vertical and centric relations. These data were then combined and used to fabricate a hybrid denture for the patient. The hybrid denture was milled from graphene-reinforced poly methyl methacrylate puck which provided the advantages of monobloc prosthesis and the material advantages of graphene. The entire prosthetic rehabilitation was completed within three appointments.